Acute hospital staff's attitudes towards dementia and perceived dementia knowledge: a cross-sectional survey in Ireland - Keogh, Brian; Drury, Amanda (My University, 2020)
R E S E A R C H A R T I C L E Open Access Acute hospital staff’s attitudes towards dementia and perceived dementia knowledge: a cross-sectional survey in Ireland Brian Keogh 1*† , Wing Ting To1†, Louise Daly1 , Geralyn Hynes1 , Siobhan Kennelly 2 , Brian Lawlor 3 , Suzanne Timmons 4 , Susan O’Reilly 5 , Mairead Bracken-Scally 6 , Aurelia Ciblis 1 , Natalie Cole7 , Amanda Drury 1 , Chiara Pittalis 8 , Brendan Kennelly 9 , Mary McCarron 1 and Anne-Marie Brady 1 Abstract Background: Little is known about staff’s attitudes in Irish acute hospital settings towards people living with dementia and their perceived dementia knowledge. The aim of this study was to understand the general level of dementia knowledge and attitudes towards dementia in different types of hospital staff, as well as to explore the potential influence of previous dementia training and experience (having a family member with dementia) and the potential moderating effects of personal characteristics. This data was required to plan and deliver general and targeted educational interventions to raise awareness of dementia throughout the acute services. Methods: A cross-sectional survey was carried out among a diverse range of hospital staff (n = 1795) in three urban acute general hospitals in Ireland, including doctors, nurses, healthcare attendants, allied professionals, and general support staff. Participants’ perceived dementia knowledge and attitudes were assessed as well as their previous dementia training and experience. To measure participant’s attitude towards dementia, the validated Approaches to Dementia Questionnaire (ADQ) was used. Results: Hospital staff demonstrated positive attitudes towards people living with dementia, and believed they had a fair to moderate understanding of dementia. Both ‘having previous dementia training’ and ‘having a relative living with dementia’ predicted attitude towards dementia and perceived dementia knowledge. Interestingly, certain personal staff characteristics did impact dementia training in predicting attitude towards dementia and perceived dementia knowledge. Conclusion: This study provides a baseline of data regarding the attitudes towards dementia and perceived dementia knowledge for hospital staff in Irish acute hospitals. The results can inform educational initiatives that target different hospital staff, in order to increase awareness and knowledge to improve quality of dementia care in Irish hospitals.
PUBLISHED
Keywords: Dementia, Staff attitudes, Acute hospital, Dementia knowledge, Approaches to dementia questionnaire